Students' selection and participation - 10th International Biennial of Illustration - The 45th Golden Pen of Belgrade, Serbia - Sofokleous, Konstantina (My University, 2026)
Four undergraduate students selected by the Biennial’s International Committee to exhibit with artwork created as assignments for Content Creation and Interactive Multimedia I Labs, at the 10th International Biennial of Illustration - The 45th Golden Pen of Belgrade, Serbia
Keywords: Arts and entertainment